Creation of a Marketplace for NFV Functions - Luís Pedro Sousa Pinto (2017)
Nowadays virtualisation has been very important worldwide because it can make network applications with the efficiency and flexibility of software applications. There are many reasons why there is investment in this type of technology. The main reasons are the financial motivation, the resource optimization and the easily migration workload. One of the virtualisation technologies that is being developed is the NFV. NFV allows the replacement and complement physical network devices with virtual network functions. Network Functions such as NAT, DNS and IMS are separated from the physical hardware for software through this technology. This thesis explains the motivation and solution of creating a Marketplace for NFV Functions. This Marketplace will be able to accelerate the Procurement process in NFV. It is defined to give customers the ability of download, compare and install VNFs to best match their needs.